1996
DOI: 10.1177/030006059602400114
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Roxithromycin in Patients with Acne

Abstract: On the basis of reports that erythromycin is effective in the treatment of acne, we investigated whether roxithromycin (ROM), a new derivative of erythromycin, might also be effective in treating acne. Roxithromycin was administered to 30 patients with acne for 8 weeks. General improvement was assessed 8 weeks after the initiation of the therapy with a six-graded scale as follows; 1: good improvement, 2: moderate improvement, 3: slight improvement, 4: no change, 5: worsening, and 6: no assessment. The percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…We have found that roxithromycin is transferred at therapeutic concentrations into acne lesions upon oral administration (data not shown), has antibacterial activity against P. acnes [5,6] and significantly inhibits in a concentration-dependent manner the 3 types of neutrophil-derived active oxygen species superoxide radical anion, hydrogen peroxide and hydroxyl radical [15]. These suggest that there is a possibility that roxithromycin is effective in the treatment of acne because it is transferred sufficiently into acne lesions in vivo, reduces bacterial load, inhibits the production of bacterial lipase and neutrophil chemotactic factor, which are extracellular inflammation-inducing agents produced by P. acnes, and inhibits the excessive production of active oxygen species caused by neutrophil migration into acne lesions.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We have found that roxithromycin is transferred at therapeutic concentrations into acne lesions upon oral administration (data not shown), has antibacterial activity against P. acnes [5,6] and significantly inhibits in a concentration-dependent manner the 3 types of neutrophil-derived active oxygen species superoxide radical anion, hydrogen peroxide and hydroxyl radical [15]. These suggest that there is a possibility that roxithromycin is effective in the treatment of acne because it is transferred sufficiently into acne lesions in vivo, reduces bacterial load, inhibits the production of bacterial lipase and neutrophil chemotactic factor, which are extracellular inflammation-inducing agents produced by P. acnes, and inhibits the excessive production of active oxygen species caused by neutrophil migration into acne lesions.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, roxithromycin has been used in the treatment of acne in Japan, with reports of efficacy in many cases [5,6]. Since March 1999, prescriptions of roxithro-mycin for the treatment of acne associated with inflammation have been covered by the National Health Insurance system.…”
Section: Introductionmentioning
confidence: 99%
“…RXM shows a potent antibacterial activity against Propionibacterium acnes, and is clinically applied for acne [33,34]. Recent study revealed that RXM has an anti-inflammatory effect by inhibiting neutrophil-derived oxygen radical generation [11].…”
Section: Discussionmentioning
confidence: 99%
“…2 More recently, treatment of acne with the macrolide antibiotic roxithromycin has been attempted. 3,4 In March 1999, the use of roxithromycin was approved in Japan for the additional indication of acne associated with inflammation, and it is recognized as a useful agent for the treatment of acne. Therefore we determined the roxithromycin concentration…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, roxithromycin is distributed to acne lesions in concentrations at which it has antibacterial activity against P. acnes. 3,4 The mechanisms by which roxithromycin affects acne vulgaris include: (i) Antibacterial action; (ii) Inhibition of production of bacterial lipases and neutrophil chemotactic factor by P. acnes (data not shown); (iii) Inhibition of the production of active oxygen species by neutrophils. 9…”
mentioning
confidence: 99%